Escherichia coli Flagellar Genes as Target Sites for Integration and Expression of Genetic Circuits - Juhas, Mario; Evans, Lewis D. B.; Frost, Joe; Davenport, Peter W.; Yarkoni, Orr; Fraser, Gillian M.; Ajioka, James W. (PLOS ONE, 2014)
E. coli is a model platform for engineering microbes, so genetic circuit design and analysis will be greatly facilitated by simple and effective approaches to introduce genetic constructs into the E. coli chromosome at well-characterised loci. We combined the Red recombinase system of bacteriophage λ and Isothermal Gibson Assembly for rapid integration of novel DNA constructs into the E. coli chromosome. We identified the flagellar region as a promising region for integration and expression of genetic circuits. We characterised integration and expression at four candidate loci, fliD, fliS, fliT, and fliY, of the E. coli flagellar region 3a. The integration efficiency and expression from the four integrations varied considerably. Integration into fliD and fliS significantly decreased motility, while integration into fliT and fliY had only a minor effect on the motility. None of the integrations had negative effects on the growth of the bacteria. Overall, we found that fliT was the most suitable integration site.